Identification of rare thalassemia variants using third-generation sequencing - Liu, Qin; Chen, Qianting; Zhang, Zonglei; Peng, Shiyi; Liu, Jing; Pang, Jialun; Jia, Zhengjun; Xi, Hui; Li, Jiaqi; Chen, Libao; Liu, Yinyin; Peng, Ying (Frontiers in Genetics, 2023)
Routine PCR, Sanger sequencing and specially designed GAP-PCR were often used in the genetic analysis of thalassemia but all of them have limitations. In this study, we evaluated a new third-generation sequencing-based approach termed comprehensive analysis of thalassemia alleles (CATSA) in the subjects with no variants identified by routine PCR, Sanger sequencing and specially designed GAP-PCR. Hemoglobin testing and routine PCR for 23 common variants were performed for 3033 subjects. Then, Sanger sequencing and specially designed GAP-PCR were performed for the subject with no variants identified by routine PCR, no iron deficiency and positive for hemoglobin testing. Finally, the new CATSA method was conducted for the subjects with no variants identified by Sanger sequencing and specially designed GAP-PCR. In the 49 subjects tested by CATSA, eight subjects had variants identified. Sanger sequencing and independent PCR confirmed CATSA's result. Besides, it is the first time that Hb Lepore was discovered in Hunan province. In total, traditional methods identified variants in 759 subjects for the 3033 subjects while CATSA identified additional variants in 8 subjects. CATSA showed great advantages compared to the other genetic testing.